Mengembangkan Kecakapan Abad 21 Mahasiswa Melalui Model Pembelajaran Inkuiri - Muhammad Qodrat Wisnu Aji (Teknodika, 2019)
According to the World Economic Forum report, the gap between the skills learned and the skills needed is widening. This has happened since the traditional learning styles have proven to fail to equip graduates with the skills they need to succeed in the world of work. Workers in the latest era need to have the skills to collaborate, communicate and solve problems (21st century skills). To meet the demands of 21st century skills there must be an important step of change, namely changing traditional teacher-centered learning patterns into student-centered learning patterns. One innovation learning model that is considered to be in line with the shift in learning paradigm is inquiry based  learning. Inquiry-based learning is the one involving students in finding important and meaningful solution through investigation and collaboration with others. Inquiry learning follows the following steps: (1)Planning, (2) retrieving, (3) processing, (4) creating, (5) sharing, and (6) evaluating. With these general principles, Inquiry-Based Learning guides the actions of 21st Century learners.Furthermore, through the inquiry process, students develop the Skill Set of 21st Century Learners skills, namely: 1) Learning and innovation consisting of critical thinking and problem solving, communication and collaboration of creativity and innovation; 2) Digital Literacy Skill consisting of information Literacy, Media Literacy and ICT Literacy; 3) Career and life skills consisting of flexibility and adaptability, self-initiative and direction, social and cross-cultural interaction, productivity and accountability, leadership and accountability